Estruturação de processos na Área de Eventos: um estudo de caso em uma empresa em Santa Maria - RS - Stefanan, Aline Armanini; Faller, Lisiane Pellini; Flores Costa, Vânia Medianeira (Revista Turismo em Análise, 2013)
The objective of this study is to structure the organizational processes at a company in the area of events in Santa Maria, RS, Brazil, in order to add value to the company and its customers by standardizing the processes. Regarding the method, the work is characterized as a qualitative descriptive case study through bibliographic research. Data collection wasperformed by local observations of activities and processes performed in the company, documentary research and informal interviews with employees, resulting in the flowcharts and standard operating procedures of the main activities of the company. It is concluded, therefore, that objective was achieved with such improvements to the company by providing the establishment of standards of daily routines and develop strategies to guide the organization in achieving its goals. It is suggested for future studies, further exploration of the area of events in the form of service companies and for the company in question, continued study of organizational processes and the development of a strategic plan.